Design and technical verification of a new type of subscriber identity module card for internet of vehicles. Issue 1 (July 2021) - Li, Yimeng; Ren, Xiaoming; Yue, Zuhui; Liu, Hui; Ding, Lanhai
Abstract: The Internet of Vehicles communication security aims to solve the V2X communication security problems under several scenarios, including direct communication and communication based on cellular network, and provides guaranteed communication security for the achievement of business goals such as vehicle-road information collaboration and road safety. Currently, V2X communication security mostly adopts digital certificate technical proposal based on public key infrastructure and is implemented through the HSM security module. However, this solution requires to preset security data such as digital certificate in the HSM module of the vehicle terminal, which has high demands on the production line of the enterprise, the difficulty is predictable. This paper designs a new type of SIM card for Internet of Vehicles based on high performance chip, which can implement the writing and updating operation of security parameters (certificates, keys, etc.) online, which can reduce the requirements for the transformation of the production line of car companies and at the same time, the security of data management is also improved. The validation result indicates that the new SIM card can realize functions such as login authentication, certificate download, signature verification, etc., and its performance meets the requirements of V2X secure communication.